2009
DOI: 10.1128/jvi.00666-08
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in gp120 Contribute to the Resistance of Human Immunodeficiency Virus Type 1 to Membrane-Anchored C-Peptide maC46

Abstract: Binding of the human immunodeficiency virus (HIV) envelope glycoprotein (Env) to the cellular CD4 receptor and a chemokine coreceptor initiates a series of conformational changes in the Env subunits gp120 and gp41. Eventually, the trimeric gp41 folds into a six-helix bundle, thereby inducing fusion of the viral and cellular membranes. C peptides derived from the C-terminal heptad repeat (CHR) of gp41 are efficient entry inhibitors as they block the six-helix bundle formation. Previously, we developed a membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 42 publications
(70 reference statements)
3
43
0
Order By: Relevance
“…These observations suggest that the A582T and L587A mutants bind CD4 but do not undergo CD4-induced conformational changes as efficiently as the wild-type Env. Of note, a previous study showed that in the context of the development of resistance to a C-peptide fusion inhibitor, the A582T change in HIV-1 Env affects C-peptide binding (42). This observation underscores the importance of this gp41 residue in modulating Env conformational transitions.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…These observations suggest that the A582T and L587A mutants bind CD4 but do not undergo CD4-induced conformational changes as efficiently as the wild-type Env. Of note, a previous study showed that in the context of the development of resistance to a C-peptide fusion inhibitor, the A582T change in HIV-1 Env affects C-peptide binding (42). This observation underscores the importance of this gp41 residue in modulating Env conformational transitions.…”
mentioning
confidence: 87%
“…Changes in the gp41 ectodomain can influence HIV-1 sensitivity to gp120 ligands, even when the gp120 epitope for those inhibitory ligands is apparently intact (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The mechanisms underlying these examples of HIV-1 neutralization escape are unknown.…”
mentioning
confidence: 99%
“…Therefore, mutations arise in the gp41 of CCR5-resistant agents (2) or the gp120 of gp41-targeting agents (27) or, as we reported, in gp41 of ADS-J1-resistant virus (3). However, taken together, our results strongly suggest that ADS-J1 is not a virus fusion inhibitor through interaction with gp41 but a gp-120 interacting compound.…”
mentioning
confidence: 99%
“…Mutations in the highly conserved amino acid motif 36 to 45 in the HR1 domain confer resistance to T20 (35), providing strong evidence that HR1 is the site of interaction of T20. However, mutations in other regions of HIV-1 envelope (Env) have been also associated with T20 resistance (26,27).…”
mentioning
confidence: 99%
“…The protein binds to the HIV-1 gp41 heptad repeat 1 region thereby interfering with six-helix bundle formation during the viral and cellular membrane fusion process. MaC46 expressing T cells are almost completely protected from HIV-1 entry and have a strong selective survival advantage compared to unmodified cells in vitro and in mouse models of HIV-1 infection (Egelhofer et al, 2004;Hermann et al, 2009a;Kimpel et al, 2010). Likewise, maC46 has been shown to be one of the most potent anti-HIV gene products currently available (Kimpel et al, 2010).…”
Section: Antiviral Proteinsmentioning
confidence: 99%